A multiresolution investigation on fatigue damage of aluminum alloys at micrometer level. (March 2017) - Chen, H; Shi, X; He, Q; Mao, JH; Liu, Y; Kang, H; Shen, J
Fatigue damage is a form of material degradation under repeated mechanical and/or thermal loading. A new multiresolution fatigue damage analysis is formulated and used to estimate low-cycle fatigue damage. The progressive fatigue damage is measured based on the X-ray computed tomography. Then, the measured microcracks and microvoids are transformed to mesoscale and macro-scale damage variables. The entire transformation process is achieved analytically by means of 3D finite element analysis and specially formulated super representative volume elements. The estimated macro-scale damage variables in terms of effective Young's moduli are compared with those measured experimentally and found to be in agreement. Some lessons learned in this study are provided for the direction of future research.